Performing invisible labour: a performance inquiry into the paradox of invisibility/visibility as experienced by domestic workers in South Africa - Lepere, Refiloe A (My University, 2021)
Performance is a slippery term. It articulates an artform as well as latent invisible forms of knowledge. This thesis uses performance as a method of research, exploring how the ‘other’ or the invisible black person comes to be seen, but also how they come to see themselves as their own material for knowledge. The study focuses on how performance is a valid mode of knowledge production by building a bridge between performance and theory in relation to domestic workers, black feminist aesthetics, personal narratives and the practice of theatremaking. It attempts to draw a connection between labour, performances of everyday work, and the imagination, and to show that performance as research is a radicalising process of knowing. I use it as a way to offer a way of reading domestic workers as knowledge creators and meaning makers of their world. By triangulating everyday performances and presentations of theatre as knowledge-making I discuss three plays I have created: (1) Between Sisters is a way of looking at the relational role of domestic worker and the counter-role of madam and how these two have been represented in various forms of art and literature; (2) Dipina Tsa Monyanyako was created with a group of domestic workers where performance was employed as a strategy for collecting data. The process of theatremaking is analysed for what an ethical performance as research exploration could look like; (3) Postcards: Bodily Preserves, is a reflective production. Here I look at the process of how as an artist I engaged in a kind of embodied non-objective research, analysing the findings through performance. In these three plays performance is used to interpret, name phenomena and frame strategies used to elicit stories, as well as to perform and rework those stories. It is a way of engaging in research that attends to critical moments that emerge in creative action (rehearsals, writing and performance) and how these can be understood as embodied data. The contribution to knowledge in this exploration of three processes/plays is that, through reflection, performance as embodied knowledge can inform a black feminist theatre-making aesthetic. I argue that theatre is a serious political platform, critical in activating communities. I emphasise that black women’s theatre aesthetic practices reveal the ‘radicalness’ of lived experiences, and is a model for rehearsing black identity in spaces of the black community
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD), 2021